2014
DOI: 10.1200/jco.2014.55.5060
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Patient-Provider Communication, Quality-of-Care Ratings, and Patient Activation Among Long-Term Cancer Survivors

Abstract: Asian survivors report poorer follow-up care communication and care quality. More research is needed to identify contributing factors beyond PPC, such as cultural influences and medical system factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 48 publications
(21 reference statements)
8
67
3
Order By: Relevance
“…First, unmeasured differences in clinical presentation and severity are most likely to drive within-physician variations in treatment. Second, the contribution of race/ethnicity and SES to differences in treatment could be the result of differences in patient-provider communication, 42,43 or differences in preferences for care. In that vein, research has shown that white and minority colorectal cancer patients have similar rates of specialty referral, yet lower rates of adjuvant treatments even after appropriate referral.…”
Section: Discussionmentioning
confidence: 99%
“…First, unmeasured differences in clinical presentation and severity are most likely to drive within-physician variations in treatment. Second, the contribution of race/ethnicity and SES to differences in treatment could be the result of differences in patient-provider communication, 42,43 or differences in preferences for care. In that vein, research has shown that white and minority colorectal cancer patients have similar rates of specialty referral, yet lower rates of adjuvant treatments even after appropriate referral.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ample evidence suggests that racial and ethnic minorities, especially blacks and Mexican-Americans, have poorer access to quality healthcare than whites in the USA. [26][27][28][29][30][31][32][33][34][35][36][37] These findings highlight the significant need to improve access to healthcare services for Mexican-Americans and blacks so that aggressively combining early detection strategies with delivery of evidencebased therapeutic interventions at early stages can help prevent CKD progression. However, caution must be used in the overall interpretation of the results stratified by race due to some small sample sizes, especially in CKD stages 3b-5.…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%
“…Under this system, KDOQI recommended avoiding glyburide treatment in stages 3-5 of CKD, and initiating treatment with other agents, using appropriate dose adjustments, and urges special care with metformin. The Kidney Disease: Improving Global Outcomes (KDIGO) updated CKD staging in 2012, accounting for the presence of albuminuria, and subdividing stage 3 into 3a (eGFR 45-59) and 3b (eGFR [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. 1 Traditionally, eGFR has been calculated with the well-established Modification of Diet in Renal Disease (MDRD) equation, which consists of four variables: age, sex, race/ ethnicity, and serum creatinine concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of patient-provider communication, cancer patients’ communication needs often go unmet (Bruinessen et al, 2013). In addition to the demonstrated gaps in the communication quality experienced by cancer patients in general, some studies report more pronounced patient-provider communication barriers among racial and ethnic minority patients (Maly, Liu, Liang, & Ganz, 2015; Palmer et al, 2014). In a qualitative study of the experiences of African American cancer patients, study participants reported dissatisfaction with the level of communication from health care providers during cancer diagnosis and treatment phases in several areas including: (1) communication of cancer information; (2) communication of shared decision making; (3) communication of empathy and understanding; and (4) communication of respect (Song, Hamilton, & Moore, 2012).…”
Section: Introductionmentioning
confidence: 99%